Development and characterization of organoclay filled polyetherimide nanocomposites for anticorrosive coatings. (2021) - James Jose, Ajith; Chacko, Francis; Wilson, Runcy; Alagar, Muthukaruppan
Abstract: Polyetherimide (PEI)/organically modified Fluorohectorite (OFH) nanocomposite were prepared by dispersing OFH in PEI matrix. The structural as well as morphological characteristics of the nanocomposites were investigated using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) and Transmission Electron Microscopy (TEM). The thermal and mechanical properties of the PEI nanocomposites were found to be significantly improved by the incorporation of organically modified flurohectorite nano clay into the PEI matrix. The water uptake of the nanocomposites was investigated in detail as a function of clay content and it was minimum for composites with 3 wt% of filler. The anticorrosion properties of clay polymer nanocomposite (CPN) coatings were evaluated by means of various electrochemical methods which include Electrochemical Impedance Spectroscopy (EIS) and Open Circuit Potential Measurements (OCP). The results obtained from various analyses showed that the PEI/OFH nanocomposites coatings possess better anticorrosion properties.